Edukasi Pengolahan Tanaman Toga Dalam Upaya Peningkatan Ketahanan Pangan Keluarga - Nur Farida Kusumawati; Budi Utomo; Yuni Rosita Dewi; Dimas Ganda; Fajar Purwanto (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2023)
Family Medicinal Plants (TOGA) are essentially nutritious plants planted in the yard and managed by the family. This type of toga plant is planted to meet the family's need for traditional medicines that can be made by yourself. Using the toga plant is an effort to prevent disease. Apart from that, this type of toga plant can also be used as a promotional effort or to improve health, as well as a curative effort as a cure for disease. Utilizing the yard around the house, or unproductive empty land through developing seed houses, planting and post-harvest and processing Toga.